Kids, Adolescents, and Young Adult Cancer Study—A Methodologic Approach in Cancer Epidemiology Research. (24th December 2009) - Link, Nancy J.; Maurer, Eva; Largent, Joan; Kent, Erin; Morris, Rebecca A.; Sender, Leonard S.; Anton-Culver, Hoda
Abstract : Advances have been made in treatment and outcomes for pediatric cancer. However adolescents and young adults (AYAs) with cancer have not experienced similar relative improvements. We undertook a study to develop the methodology necessary for epidemiologic cancer research in these age groups. Our goal was to create the Kids, Adolescents, and Young Adults Cancer (KAYAC) project to create a resource to address research questions relevant to this population. We used a combination of clinic and population-based ascertainment to enroll 111 cases aged 0–39 for this methodology development study. The largest groups of cancer types enrolled include: breast cancer, leukemia, lymphoma, and melanoma. The overall participation rate is 69.8% and varies by age and tumor type. The study included patients, mothers, and fathers. The methods used to establish this resource are described, and the values of the resource in studies of childhood and young adult cancer are outlined.